Human slan (6-sulfo LacNAc) dendritic cells are inflammatory dermal dendritic cells in psoriasis and drive strong TH17/TH1 T-cell responses - Hänsel, Anja; Günther, Claudia; Ingwersen, Jens; Starke, Josephine; Schmitz, Marc; Bachmann, Michael; Meurer, Michael; Rieber, Ernst Peter; Schäkel, Knut (The journal of allergy and clinical immunology, 2011)
Background - Psoriasis is a chronic inflammatory skin disease that is considered to result from activated T cells stimulated by a population of inflammatory dermal dendritic cells (DCs). The origin and identity of these inflammatory dermal DCs are largely unknown. - Objective - We previously identified slanDCs (6-sulfo LacNAc) DCs as a rich source of TNF-α and as the early major source of IL-12. Here we studied the relevance of slanDCs as inflammatory dermal DCs in psoriasis. - Methods - Psoriasis skin samples were stained for the presence of activated slanDCs. Functional studies were carried out to determine the cytokine production of slanDCs, their Th17/Th1 T-cell programming, and their migration behavior. - Results - Large numbers of IL-23, TNF-α, and inducible nitric oxide synthase expressing slanDCs were found in psoriatic skin samples, which can be recruited by C5a, CX3CL1, and CXCL12. SlanDCs isolated from blood produced high levels of IL-1ß, IL-23, IL-12, and IL-6. Compared with classic CD1c+ DCs, slanDCs were far more powerful in programming Th17/Th1 T cells that secrete IL-17, IL-22, TNF-α, and IFN-γ, yet CD1c+ DCs induced a higher IL-10 production of T cells. Self-nucleic acids complexed to cathelicidin LL37 trigger endosomal Toll-like receptor (TLR) signaling (TLR7, TLR8, TLR9) and are key factors for the activation of DCs in psoriasis. We show that slanDCs respond particularly well to complexes formed of self-RNA and LL37. Similarly, slanDCs stimulated with a synthetic TLR7/8 ligand produced high levels of proinflammatory cytokines. - Conclusion - Our study defines slanDCs as inflammatory dermal DCs in psoriasis and identifies their strong capacity to induce Th17/Th1 responses.